PERHITUNGAN HARGA POKOK PRODUKSI DALAM MENENTUKAN HARGA JUAL PADA UD. LUQMAN BINTANG JAYA SIDOARJO - Zahra Zulfiana Said; Fia Rahma; Nuzulul Fatimah (JURNAL KINDAI, 2026)
This study aims to analyze the cost of goods manufactured and the selling price at UD. Luqman Bintang Jaya. The research method is a descriptive qualitative case study. The data used are primary (interviews with the company owner, the head of production, and production employees) and secondary (archive documents of COGS calculations). The results show that the company's cost of goods manufactured is lower than that calculated under the job order costing method by Rp2,633/pair. The cost of goods manufactured, calculated using the company's method, is Rp11,850/pair, while the cost calculated using the job-order costing method is Rp14,483/pair. This is because the company has not included detailed factory overhead costs. The company's selling price is lower than the manufacturer's, by Rp3,650/pair. The company's selling price is Rp16,250/pair, while the price determined using the manufacturer's method is Rp19,900/pair. Setting a high selling price makes the product less competitive, while a too low selling price results in losses. Keywords: cost of goods manufactured; job order costing method; selling price determination